2013
DOI: 10.1002/phar.1169
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Conivaptan Bolus Dosing in Hyponatremic Neurosurgical Patients

Abstract: We recommend a single 20-mg dose of conivaptan as the preferred initial approach to treating patients with SIADH who are in the neurosurgical intensive care unit. The 24-hour natremic response should then dictate whether additional doses of conivaptan or other therapeutic interventions are required. We believe that such an approach is safe and will result in a controlled and predictable increase in the serum sodium concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…To our knowledge, this is the largest study describing the effectiveness and tolerability of conivaptan and tolvaptan for the correction of hyponatremia in neurocritically ill patients. Our observations support the findings of other studies that reported that single doses of vaptans led to an increase in serum sodium level in neurocritically ill patients . Our study demonstrated that vaptans led to an increase in mean serum sodium level of 5.2–7.9 mEq/L at 24 hours that was sustained up to 96 hours after the last dose.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…To our knowledge, this is the largest study describing the effectiveness and tolerability of conivaptan and tolvaptan for the correction of hyponatremia in neurocritically ill patients. Our observations support the findings of other studies that reported that single doses of vaptans led to an increase in serum sodium level in neurocritically ill patients . Our study demonstrated that vaptans led to an increase in mean serum sodium level of 5.2–7.9 mEq/L at 24 hours that was sustained up to 96 hours after the last dose.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations support the findings of other studies that reported that single doses of vaptans led to an increase in serum sodium level in neurocritically ill patients. [10][11][12][13]15 Our study demonstrated that vaptans led to an increase in mean serum sodium level of 5.2-7.9 mEq/L at 24 hours that was sustained up to 96 hours after the last dose.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations